Tindak Tutur Direktif Pada Banner di Jalanan Wilayah Kecamatan Bojonegoro: Kajian Pragmatik - Yulika Gita Rahayu Ningtyas; Suhartono; Abdul Kholiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the form and function of directive speech on banners on the streets of Bojonegoro District in a pragmatic study. This study uses a qualitative approach with a descriptive method to understand the use of language in the context of public communication. The research data is in the form of words, phrases, and sentences that contain directive speech actions on banners, which are collected through listening, documentation, and recording techniques in various strategic locations. The data is then analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that there are seven forms of directive speech, namely orders, prohibitions, requests, invitations, appeals, platitudes, and questions. The most dominant forms are commands, prohibitions, and invitations, which indicate that banners are widely used to direct, control, and influence people's actions. In addition, these forms are conveyed with varied language strategies, both directly and indirectly, and pay attention to the level of politeness. In terms of function, directive speech on banners has persuasive, regulative, educational, and preventive functions. Commands and prohibitions tend to function to control behavior directly, while invitations, appeals, and requests emphasize a polite persuasive approach so that they are easily accepted by the community. Thus, banners as a medium of public communication not only function as a conveyor of information, but are also effective in shaping and influencing people's social behavior through the use of short, concise, and communicative language.